AMAP Progress report to the SAO meeting in Yellowknife, October 2014. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2014)
Progress report from the Arctic Council working group Arctic Monitoring and Assessment Programme (AMAP). Submitted to the Senior Arctic Officials meeting in Yellowknife, CAnada, October 22-23 2014.